Into the Wild: Neuroergonomic Differentiation of Hand-Held and Augmented Reality Wearable Displays during Outdoor Navigation with Functional Near Infrared Spectroscopy - McKendrick, Ryan; Parasuraman, Raja; Murtza, Rabia; Formwalt, Alice; Baccus, Wendy; Paczynski, Martin; Ayaz, Hasan (Frontiers in Human Neuroscience, 2016)
Highly mobile computing devices promise to improve quality of life, productivity, and performance. Increased situation awareness and reduced mental workload are two potential means by which this can be accomplished. However, it is difficult to measure these concepts in the ‘wild’. We employed an ultra-portable battery operated and wireless functional near infrared spectroscopy (fNIRS) to non-invasively measure hemodynamic changes in the brain’s prefrontal cortex. Measurements were taken during navigation of a college campus with either a hand-held display, or an augmented reality wearable display. Hemodynamic measures were also paired with secondary tasks of visual perception and auditory working memory to provide behavioral assessment of situation awareness and mental workload. Navigating with an augmented reality wearable display produced the least workload during both secondary tasks. The hemodynamics associated with errors were also different between the two devices. Errors with an augmented reality wearable display were associated with increased prefrontal activity and the opposite was observed for the hand-held display. This suggests that the cognitive mechanisms underlying errors between the two devices differ. These findings show fNIRS is a valuable tool for assessing new technology in ecologically valid settings and that head-mounted displays offer benefits with regards to mental workload while navigating, and potentially superior situation awareness with improved display design.